A Survey on Temporal Changes of Drinking Water Quality in Urban Areas Using Iran Resources Water Quality Index and Statistical Analysis: A Case Study of Shiraz, Iran, 2011-2015 - Mohammad Ali Baghapour; Zohre Moeini; Yousef Kamali; Mohammad reza Shooshtarian; Mohammad Reza Zare (Shiraz University of Medical Sciences, 2017)
Background: Monitoring the water quality and analyzing its changes over time is an important aspect of sustainable management and development of water resources. The purpose of the present study was to analyze the trend of temporal variations in the quality of drinking water supplied from groundwater sources in Shiraz, using IRWQI (Iran Water Quality Index) as well as statistical analysis.Methodology: This study was conducted on groundwater resources in Shiraz, Iran from 2011 to 2015. 10 water quality parameters were used in this index including NO3, Fecal Coliform, EC, TH, SAR, BOD5, PO4, COD, pH, and DO, with their own weights. Repeated measure test was used in order to analyze the differences between IRWQI values between the study years.Results: The results showed that IRWQI varied between 89/96 (very good quality) and 49/51 (average quality) in the study years. The main causes of water quality decline were average to relatively high levels of hardness and nitrate. The general pattern of the changes in water quality has been accompanied by an increase and decrease, so that the water quality has improved from 2011 to 2013 but then declined until the end of the study.Conclusion: Regarding the necessity of clarifying the water quality condition and its changes and the importance of using IRWQI as an emerging national indicator, water quality analysis in different parts of the country, taking advantage of this indicator and statistical analyses will help the country promote and accelerate the integrated management of water resources quality.